If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 32 + -1(3x + -2(2x + -3)) = 183 Reorder the terms: 32 + -1(3x + -2(-3 + 2x)) = 183 32 + -1(3x + (-3 * -2 + 2x * -2)) = 183 32 + -1(3x + (6 + -4x)) = 183 Reorder the terms: 32 + -1(6 + 3x + -4x) = 183 Combine like terms: 3x + -4x = -1x 32 + -1(6 + -1x) = 183 32 + (6 * -1 + -1x * -1) = 183 32 + (-6 + 1x) = 183 Combine like terms: 32 + -6 = 26 26 + 1x = 183 Solving 26 + 1x = 183 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-26' to each side of the equation. 26 + -26 + 1x = 183 + -26 Combine like terms: 26 + -26 = 0 0 + 1x = 183 + -26 1x = 183 + -26 Combine like terms: 183 + -26 = 157 1x = 157 Divide each side by '1'. x = 157 Simplifying x = 157
| 40-4(x-3)=7x-5 | | 4(f-5)=-24 | | 2cos^2x=coax | | 32x^2+48x^4=0 | | 8.56x+51.36=102.72 | | -26.7+3.4r=4.4(r-6) | | D(20)=22g | | -10(s+2)=53 | | 6a+11=28+83 | | 9999999999999-24533357= | | Y=4x-260 | | 2x+2x+2=4x+4 | | X+2=10+5x | | 45a+35= | | 7x+-3=39 | | D(10.5)=22g | | 8c-7= | | 3(x-4)squre=27 | | (5m-7)+9m= | | 3(x-4)square=27square | | 3(x-4)=27square | | X-10=101 | | -2x+2=4x+68 | | 2(x+3)=6x-4(x-1.5) | | 3(20-b)=26 | | x(2x-2)+x(5x-2)=(7x+8)(x-2) | | 8+2n-1= | | 21n(5x)=10 | | 5m-4n= | | 14-3c=1 | | 13x+5yi=-52+40i | | 15x^2+9c=0 |